Case of Barrett's adenocarcinoma with marked endoscopic morphological changes in Barrett's esophagus over a long follow‐up period of 15 years. Issue 5 (5th April 2016) - Iwaya, Yugo; Yamazaki, Tomoo; Watanabe, Takayuki; Seki, Ayako; Ochi, Yasuhide; Hara, Etsuo; Arakura, Norikazu; Tanaka, Eiji; Hasebe, Osamu
Abstract : The natural history of Barrett's esophagus (BE) is unclear. We herein describe a case of Barrett's adenocarcinoma (BAC) in which we could closely observe marked morphological changes in BE over a long follow‐up period of 15 years. A man in his seventies received routine esophagogastroduodenoscopy (EGD) and was diagnosed as having reflux esophagitis and short‐segment BE. The BE gradually became elongated, and BAC was detected 9 years following the initial EGD examination with continued administration of a proton pump inhibitor. We witnessed that BE elongated sporadically over time and mucosal breaks of reflux esophagitis were detectable several years before elongation. The patient underwent endoscopic submucosal dissection for BAC and has been monitored by EGD every year thereafter. These remarkable morphological changes may be representative of the natural history of BE and aid in deciding long‐term disease management.